EFFECTS OF MODIFIED ULTRAFILTRATION ON BLOOD PRODUCTS REQUIREMENT IN CHILDREN UNDERGOING OPEN HEART SURGERY - Tariq, Muhammad; Musaddiq, Yasmin; Naqvi, Shahab; Novick, William M.; Qayyum, Mazhar (Pakistan Armed Forces Medical Journal, 2018)
Objective:  To find out the effects of modified ultrafiltration on blood products requirement for transfusion in congenital heart disease children after open heart surgery. Design:  This was a quasi-experimental study between two clinical groups. Patients were assigned to both groups by using convenient sampling; to do Modified Ultrafiltration or not  was surgeon’s preference who was unaware whether the patient is participating in any study or not.Place and Duration of Study:  The study was carried out at Armed Forces Institute of Cardiology/National Institute of Heart Diseases (AFIC/NIHD) Rawalpindi between August, 2005 and September, 2006.Patients and Methods:  Total 200 patients were included in this study and were divided equally into two groups; study group (MUF) and control group (non MUF) keeping hundred patients in each group.Results:  Significantly increased level of hemoglobin after MUF (9.7±1.4 gm/dl before MUF versus 13.6±1.6 gm/dl after MUF, p